2019
DOI: 10.1021/acssuschemeng.9b02502
|View full text |Cite
|
Sign up to set email alerts
|

Polyethers as Complexing Agents in Calcium-Catalyzed Cyclic Carbonate Synthesis

Abstract: Herein, we report a detailed investigation of alkali and alkaline earth metal salts in combination with polyethers as catalytic systems for the synthesis of cyclic carbonates from epoxides and CO2. CaI2 showed superior activity compared to various other tested alkali and alkaline earth metal salts. Interestingly, in contrast to other catalytic protocols, the presence of hydroxyl groups hampered the reaction. Thus, poly­(ethylene glycol) dimethyl ethers (PEG DME) proved to be the most suitable polymer complexin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 90 publications
(138 reference statements)
1
32
0
Order By: Relevance
“…Finally, an epoxide based on dicyclopentadiene was successfully converted to the corresponding cyclic carbonate where only one of the epoxides is selectively converted (Table 3, 24 b ). This selectivity has previously been observed by the few groups that have attempted conversion of this challenging substrate [5b,20,29,30] . In summary, increasing the reaction temperature, allows for the successful conversion of more complex substrates.…”
Section: Resultssupporting
confidence: 67%
“…Finally, an epoxide based on dicyclopentadiene was successfully converted to the corresponding cyclic carbonate where only one of the epoxides is selectively converted (Table 3, 24 b ). This selectivity has previously been observed by the few groups that have attempted conversion of this challenging substrate [5b,20,29,30] . In summary, increasing the reaction temperature, allows for the successful conversion of more complex substrates.…”
Section: Resultssupporting
confidence: 67%
“…Whereas most coordination compounds of calcium are generally insoluble in most reaction media, Werner et al showed that the use of chelating ligands (crown ethers) in combination with calcium halides leads to soluble and highly active Lewis acids for CO 2 /epoxide cycloaddition. 118,209,[280][281][282] The in situ complexation of CaI 2 by poly(ethylene glycol)dimethyl ether (PEG-DME-500) further promotes the nucleophilicity of the iodide anion leading to a system able to mediate the cycloaddition of CO 2 to terminal and internal epoxides including iEFA1 (entry 4, Table 6). 280 Alternatively, crown ethers are effective complexing agents for CaI 2 leading to highly active calcium catalysts such as 4 for the cycloaddition of CO 2 to terminal epoxides under ambient conditions.…”
Section: Catalytic Performance Of Binary Catalytic Systems In the Cycloaddition Of Co 2 To Iefa1: Metal Salts And Coordination Compoundsmentioning
confidence: 99%
“…Addition of metal‐based Lewis acidic complexes to nucleophilic quaternary salts has the effect to strongly accelerate carbonation of internal epoxides; Fe(II) bispincer‐type, V(V) and Al(III) aminotriphenolate complexes were reported to promote the carbonation of epoxidized methyl oleate (EMO) in the 70–100 °C temperature range under 5–10 bar CO 2 in presence of nucleophilic halide salts. Use of CaI 2 /PPh 3 /dicyclohexyl‐functionalized 18‐crown‐6 ether (DCFCE) led to carbonation of EMO at low temperature (45 °C) under 10 bar CO 2 pressure . Similarly, efficient Al(III) and La(III) complexes were reported as Lewis acids for carbonation of limonene monoxide under mild conditions (70–85 °C, 10 bar CO 2 ).…”
Section: Introductionmentioning
confidence: 99%